2014
DOI: 10.1080/02640414.2014.981846
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the SenseWear Armband in different ambient temperatures

Abstract: This study examines the validity of the SenseWear Armband in different temperatures using the old (SenseWear v2.2) and newest version of the algorithm (SenseWear v5.2) against indirect calorimetry (IC). Thirty-nine male and female students (21.1 ± 1.41 years) completed an exercise trial in 19°C, 26°C and 33°C consisting of 5 min standing followed by alternating walking/running at 35% and 65% of their maximal oxygen uptake. The accuracy of the algorithms was evaluated by comparing estimated energy expenditure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 45 publications
(52 reference statements)
3
23
0
Order By: Relevance
“…We are aware of only three published reports that compared the newest algorithm v5.2 with previous v2.2 for estimating energy expenditure during physical activity (Lee et al, 2014; Smith et al, 2012; Van Hoye et al, 2014). Van Hoye et al (Van Hoye et al, 2014) reported that SenseWear v5.2 did not improve energy expenditure estimation in young men and women while standing, walking, or running on a treadmill during indoor temperatures of 19° C and 26° C, but did improve energy expenditure estimation while walking and running at 33° C. Smith et al (Smith et al, 2012) studied pregnant women while they performed seven different activities (typing, folding laundry, sweeping, walking at 0.89, 1.12, and 1.34 m·s −1 and walking at 1.34 m·s −1 up a 3% incline).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We are aware of only three published reports that compared the newest algorithm v5.2 with previous v2.2 for estimating energy expenditure during physical activity (Lee et al, 2014; Smith et al, 2012; Van Hoye et al, 2014). Van Hoye et al (Van Hoye et al, 2014) reported that SenseWear v5.2 did not improve energy expenditure estimation in young men and women while standing, walking, or running on a treadmill during indoor temperatures of 19° C and 26° C, but did improve energy expenditure estimation while walking and running at 33° C. Smith et al (Smith et al, 2012) studied pregnant women while they performed seven different activities (typing, folding laundry, sweeping, walking at 0.89, 1.12, and 1.34 m·s −1 and walking at 1.34 m·s −1 up a 3% incline).…”
Section: Discussionmentioning
confidence: 99%
“…Van Hoye et al (Van Hoye et al, 2014) reported that SenseWear v5.2 did not improve energy expenditure estimation in young men and women while standing, walking, or running on a treadmill during indoor temperatures of 19° C and 26° C, but did improve energy expenditure estimation while walking and running at 33° C. Smith et al (Smith et al, 2012) studied pregnant women while they performed seven different activities (typing, folding laundry, sweeping, walking at 0.89, 1.12, and 1.34 m·s −1 and walking at 1.34 m·s −1 up a 3% incline). This is comparable to our structured routine, albeit with a narrower range of indirect calorimetry-measured energy expenditure (≈1-5 kcal·min −1 vs. ≈1-9 kcal·min −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations